1999
DOI: 10.1086/314540
|View full text |Cite
|
Sign up to set email alerts
|

Quality and Quantity of the Humoral Immune Response in Healthy Elderly and Young Subjects after Annually Repeated Influenza Vaccination

Abstract: Doubt about the serologic efficacy of annually repeated influenza vaccination prompted investigations into the course of hemagglutination-inhibiting (HI), IgG, and IgA antibody titers and the IgG and IgA avidity index to influenza A/Taiwan/1/86 and A/Beijing/353/89 after annual vaccination. Fifty-four healthy elderly persons >70 years of age and 24 healthy young adults <30 years of age received standard influenza vaccine during 3 consecutive years. On average, prevaccination HI, IgG, and IgA titers to both inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
70
1
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(78 citation statements)
references
References 28 publications
4
70
1
3
Order By: Relevance
“…In contrast, most subjects in the present study had received the study vaccine strain in both pre-study years and, as annual vaccine recipients, could have received B/Victoria lineage strains in 4 of 5 prestudy years. As others have reported, 15,16,24 repeated vaccination of seniors with the same or similar antigens causes titers to approach maximal levels. Our observations of high baseline B/Brisbane titers and limited further responses to vaccination are consistent with this phenomenon, although subjects had also received A/H1N1/California/2009 antigen in both pre-study years without a similar increase in baseline titers.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…In contrast, most subjects in the present study had received the study vaccine strain in both pre-study years and, as annual vaccine recipients, could have received B/Victoria lineage strains in 4 of 5 prestudy years. As others have reported, 15,16,24 repeated vaccination of seniors with the same or similar antigens causes titers to approach maximal levels. Our observations of high baseline B/Brisbane titers and limited further responses to vaccination are consistent with this phenomenon, although subjects had also received A/H1N1/California/2009 antigen in both pre-study years without a similar increase in baseline titers.…”
Section: Discussionmentioning
confidence: 58%
“…13 This study benefitted from a high degree of similarity among the study groups, effectively controlling for a range of potential influences on responses to vaccination including age, 19 sex, prior influenza vaccination, 15,16 frailty, 20 chronic health conditions, obesity, 21 moderate exercise 22 and probiotic use. 23 Similarity of baseline antibody titers among the study groups avoided the need for adjustment of observed responses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Influenza vaccination in the previous year was associated with a lower seroconversion rate to A/H1N1; both vaccines contained the same A/H1N1 strain. The effects of previous influenza vaccination on antibody responses remain subject to discussion, because some studies demonstrated decreased antibody responses (34)(35)(36), whereas others showed similar (37)(38)(39) or improved responses (40).…”
Section: Discussionmentioning
confidence: 99%